Application of Use Juice Leaf Jackfruit (Artocarpus heterophyllus) as Natural Disinfectant in Poultry Incubator on Decreasing Number and Zona Resistor of Bacteria - Yuli Astuti Hidayati; E. T. Marlina; D. Z. Badruzzaman (Jurnal Ilmu Ternak, 2017)
ABSTRACTThis study aims to examine the effect of the use of jackfruit leaf juice as a natural disinfectant to decrease the amount and the inhibition of bacteria in incubator. The method used in this research is experimental method in laboratory using Completely Randomized Design with 3 treatments and 6 replications. The three treatments are P1 = juice of jackfruit leaf with dilution 75% (25% concentration), P2 = juice of jackfruit leaf with 50% dilution (50% concentration), and P3 = juice of jackfruit leaves with 25% dilution (75% concentration). Data were analyzed by means of verbalization and to know the difference between treatments was done by Duncan test. The results showed that the juice solution of jackfruit leaves contain phenol compounds namely flavonoids, saponins and tannin compounds which are anti microbial substances. Treatment of P3 (75%) decreased the number of bacteria as much as 82.54% and the widest drag 0.3 cm for bacteria coccus and 0.5 cm for bacteria bacil.